EDUCATIONAL TOURISM AS A POTENTIAL FOR THE DEVELOPMENT OF THE REGION (Web of Teachers: Inderscience Research, 2024)
The article shows the specifics of building an educational tourism system as a potential for the development of the Tyumen region's education system and improving the investment climate. The main results of the implementation of the regional projects in three areas of educational tourism: educational tours, the "Culture of Life" project, projects in the field of socialization and education. Some educational routes are described, the specifics of conducting "the lessons outside the walls of school" and "the lessons at the different companies", the creation of corporate classes from leading industrial partners of the Tyumen region, a new look at the implementation of the technologies lessons, attracting and consolidating young people in rural areas in the agro-industrial sector of the economy and other projects.